2014
DOI: 10.1103/physrevc.90.045202
|View full text |Cite
|
Sign up to set email alerts
|

Role of diquark correlations and the pion cloud in nucleon elastic form factors

Abstract: Electromagnetic form factors of the nucleon in the space-like region are investigated within the framework of a covariant and confining Nambu-Jona-Lasinio model. The bound state amplitude of the nucleon is obtained as the solution of a relativistic Faddeev equation, where diquark correlations appear naturally as a consequence of the strong coupling in the colour3 qq channel. Pion degrees of freedom are included as a perturbation to the "quark-core" contribution obtained using the Poincaré covariant Faddeev amp… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
132
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 75 publications
(142 citation statements)
references
References 117 publications
(203 reference statements)
8
132
2
Order By: Relevance
“…Work by Miller et al, Lin et al, and Cloet et al [16][17][18] has reproduced the experimentally observed momentum dependence of F 2 . These calculations emphasize the importance of the quark wave functions, i.e.…”
Section: Introductionsupporting
confidence: 59%
“…Work by Miller et al, Lin et al, and Cloet et al [16][17][18] has reproduced the experimentally observed momentum dependence of F 2 . These calculations emphasize the importance of the quark wave functions, i.e.…”
Section: Introductionsupporting
confidence: 59%
“…3.12. Studies on the impact of pion cloud effects in this framework (also in the quark-diquark approximation) can be found in [345,346]. Results for the genuine three-body system have not been published so far.…”
Section: Approximations and Truncationsmentioning
confidence: 99%
“…For example, the rainbow-ladder truncation becomes a vector-vector contact interaction and in the quark-diquark equation an additional static approximation for the exchange quark propagator is made. The NJL model was recently employed to calculate elastic nucleon and hyperon form factors [346,507], building upon a body of work on other structure properties such as parton distribution functions and nuclear medium effects; see also [508] and references therein. Closely related is the contactinteraction model developed in Refs.…”
Section: B Kinematics Andmentioning
confidence: 99%
“…Here the proper-time scheme is chosen, because it simulates aspects of quark confinement by eliminating on-shell quark propagation, while maintaining the symmetries of the theory, such as the Poincaré and chiral symmetries. As a result it has been widely used [38,39,51,[59][60][61][62][63][64]. Formally the proper-time regularization scheme is defined by…”
Section: Nambu-jona-lasinio Modelmentioning
confidence: 99%
“…For example, the NJL model encapsulates dynamical chiral symmetry breaking (DCSB), which gives rise to dynamically generated dressed quark masses. The NJL model has been successfully used to investigate a broad range of phenomena, including hadron properties [12,[46][47][48][49][50][51][52], heavy ion collisions [53], neutron stars [45,54,55], quark fragmentation functions [56,57] and transverse momentum dependent phenomena [58].…”
Section: Nambu-jona-lasinio Modelmentioning
confidence: 99%